Pengaruh Pemberian Reinforcement (Penguatan) oleh Guru PAK terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 3 Pangaribuan Tahun Pembelajaran 2023/2024 - Liana Limbong; Maringan Sinambela; Frainskoy Rio Naibaho; Robinhot Sihombing; Malani Simanungkalit (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine whether there is a positive and significant effect of giving reinforcement on student learning motivation at SMP Negeri 3 Pangaribuan in the 2023/2024 Learning Year. This study uses a quantitative approach with a population of all VIII graders at SMP Negeri 3 Pangaribuan totaling 110 people with a sample of 44 people. Data were collected with a questionnaire of 35 items compiled by the author based on variable indicators according to theory. The questionnaire test was conducted on 30 students in the same place, namely SMP Negeri 3 Pangaribuan, the questionnaire of variable x was tested and it was found that all items were valid. With the validity test rcount (0.40 - 0.69) > rtable (0.05,30) = 0.361 and the reliability of the questionnaire test which is at a value of 0.883190. The results of the validity of the questionnaire test of variable y with the validity test rcount (0.38 - 0.78) > rtable (0.05,30) = 0.361 and the reliability of the questionnaire test which is at a value of 0.8558508.